2023
DOI: 10.1038/s41467-023-38271-5
|View full text |Cite
|
Sign up to set email alerts
|

Germline modifiers of the tumor immune microenvironment implicate drivers of cancer risk and immunotherapy response

Abstract: With the continued promise of immunotherapy for treating cancer, understanding how host genetics contributes to the tumor immune microenvironment (TIME) is essential to tailoring cancer screening and treatment strategies. Here, we study 1084 eQTLs affecting the TIME found through analysis of The Cancer Genome Atlas and literature curation. These TIME eQTLs are enriched in areas of active transcription, and associate with gene expression in specific immune cell subsets, such as macrophages and dendritic cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 180 publications
0
14
0
Order By: Relevance
“…The response of tumors derived from the parental B2905 cell line to ICB treatment was determined in a preclinical study described previously 34 . Briefly, mice bearing tumors grown from implanted parental B2905 cells were subjected to anti-CTLA-4 or control IgG treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The response of tumors derived from the parental B2905 cell line to ICB treatment was determined in a preclinical study described previously 34 . Briefly, mice bearing tumors grown from implanted parental B2905 cells were subjected to anti-CTLA-4 or control IgG treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Solid tumors have a highly complex immune environment that is extensively infiltrated with immune cells. , Macrophages play a vital role in the TME because of their high numbers and intricate functions . TAMs could serve as an indicator of regional and systemic cues that promote tumor cell growth, survival, and migration .…”
Section: Resultsmentioning
confidence: 99%
“…Germline genetic factors exert significant influence on immune homeostasis and our immunological status 17,124 . The variability in the onset and severity of irAEs observed among patients receiving similar ICI agents can be partially attributed to germline genetic variation in immune function 17,124 .…”
Section: Mechanisms Of Ici‐induced Iraes In Nsclcmentioning
confidence: 99%
“…Germline genetic factors exert significant influence on immune homeostasis and our immunological status 17,124 . The variability in the onset and severity of irAEs observed among patients receiving similar ICI agents can be partially attributed to germline genetic variation in immune function 17,124 . Recent research has demonstrated a correlation between polygenic germline risk for autoimmune conditions and the development of cutaneous and thyroid irAEs in NSCLC 125,126 .…”
Section: Mechanisms Of Ici‐induced Iraes In Nsclcmentioning
confidence: 99%